INTEGRATION OF NEUROMUSCULAR ADAPTATION AND COGNITIVE STRATEGIES IN THE TRAINING OF JUDOKAS FOR COMPETITIVE ACTIVITY (World Bulletin of Physical Education and Sports Science, 2025)
This article explores the complex interplay between neuromuscular adaptation and cognitive strategies in the training of judokas for competitive activity. The research emphasizes how modern sports science, neurophysiology, and cognitive psychology can be integrated to enhance performance, reaction time, tactical flexibility, and overall resilience during competition. It examines how specific training methods targeting neural pathways, proprioception, and sensorimotor coordination contribute to the optimization of technical and tactical execution in judo. The study also analyzes the influence of cognitive load, decision-making, and situational awareness on the athlete’s ability to anticipate and respond effectively to opponents’ movements. The integration of mental training and biomechanical conditioning is discussed as a synergistic model aimed at achieving sustainable performance under stress. The findings reveal that a multidimensional training approach, combining motor control exercises, visualization techniques, neurofeedback, and reaction-based drills, significantly improves neuromuscular synchronization and cognitive efficiency. The research concludes that understanding and managing the interaction between neuromuscular systems and cognitive functions is key to developing judokas capable of high-level adaptive performance in unpredictable competitive environments.
Keywords: neuromuscular control with cognitive processes such as anticipation, decision-making, and situational awareness. This interdependence of body and mind reflects